Overtime Working in an Unregulated Labour Market - David N.F. Bell; Robert A. Hart (Institute for the Study of Labor (IZA), 1999)
Using individual-level data on male non-managerial workers from the 1996 British New Earnings Survey, we estimate overtime hours and average premium pay equations. Among other issues, four broad questions are of central importance. (a) What are the impacts of straight-time pay and hours on overtime pay and hours? (b) Is premium pay positively related to the length of weekly overtime? (c) What is the influence of collective bargaining coverage on overtime pay and hours? (d) Does overtime working serve significantly to alter wage earnings differentials between covered and uncovered workers? These and other issues are discussed comparatively in relation to unregulated British overtime working practices and to the United States were overtime is subject to mandatory rules.
Keywords: J38; J33; 330; Overtime; collective bargaining; labor market regulation; Überstunden; Leistungsorientierte Vergütung; Lohnstruktur; Tarifpolitik; Arbeitszeitflexibilisierung; Großbritannien; USA